Adsorption mechanism of new mixed anionic/cationic collectors in a spodumene-feldspar flotation system. (8th June 2017) - Tian, Jia; Xu, Longhua; Deng, Wei; Jiang, Hao; Gao, Zhiyong; Hu, Yuehua
Graphical abstract: Highlights: The flotation performance of the mixed NaOL/DTAC was exhibited. The properties of the mixed micelles NaOL/DTAC were illustrated. The synergism of the mixed NaOL/DTAC was investigated. The adsorption mechanism of the mixed NaOL/DTAC was investigated. Abstract: The mixed anionic collector sodium oleate (NaOL) and cationic collector dodecyl ammonium chloride (DTAC) demonstrate high selectivity for the flotation of spodumene from feldspar, and the optimal molar ratio of NaOL and DTAC is 9:1. To detect the underlying mechanism, surface tension measurements, adsorption measurements, zeta potential measurements and Fourier transform infrared (FTIR) analyses were performed. The surface and thermodynamic parameters (CMC, γCMC, Γmax, Amin, Δ G m 0 ) obtained from surface measurements show higher surface activity and a denser molecular arrangement in mixed NaOL/DTAC than in single NaOL or DTAC. Further analysis of the interaction parameters and activity coefficients ( β m, β σ, f m, and f σ ) obtained from the theory of regular solutions shows that there is a synergistic effect both in the mixed micelle and at the water/air interface. Moreover, the maximum synergistic interaction was found at XDTAC = 0.5 in mixed NaOL/DTAC. The adsorption measurements show that more NaOL is adsorbed on the spodumene surface than on feldspar and that the cationic collector can improve the adsorption of NaOL on the spodumene surface by a small amount, but not for feldspar. The zeta potential measurement and Fourier transform infrared analyses show that in the mixed NaOL/DTAC system, the anionic collector NaOL first reacts with aluminum sites on the mineral surface. Then, the cationic collector DTAC forms an electroneutral complex with the anionic collector NaOL and co-adsorbs on the Stern layer because of the chemisorption of NaOL. Based on these analyses, an adsorption model of the mixed collector NaOL/DTAC on the mineral surface was drawn.